Phase Change Properties in Chalcogenide Semiconductors - M. Batpurev,; J. Battogtokh, (Scientific transaction of the National University of Mongolia. Physics, 2022)
Since the discovery of chalcogenide semiconductors in 1955 at Ioffe Institute, it had passed half a century. During this time the unique properties of chalcogenide semiconductors were extensively studied, which had found many technical applications. In the past decades has seen an explosion of new interest to the chalcogenide semiconductors, due to their use as media for optical and electrical recording information based on “glass-crystal” phase transition. The properties of a high-resistance state (“OFF” state) and low-resistance state (“ON” state), which is resulting from the switching effect, i.e. phase change and nonlinearity of the current-voltage characteristics are studied intensively in recent year. In this research work, we studied the properties of phase change in chalcongenide semiconductors. Calculations was made by using Matlab.